The quest for the autochthonous in Hispanoamerican cinema - Cadavid, Alvaro (Íkala, Revista de Lenguaje y Cultura, 2001)
The author presents a view of Latin American cinema in the 20th century. The directors' reflections on the esthetic activity and their analyses of the sociocultural reality of each country represent one of the main characteristics of the Latin American cinema: the search for an identity. Another issue addressed is the complementarity between the literary and the cinematographic creations which allowed the rise of native forms of narration, a way toward decolonization. This article is an excerpt of the author's work that received the National Culture Award Universidad de Antioquia 2001. How to reference this article: Cadavid, A. (2001). La búsqueda de lo propio en el cine hispanoamericano. Íkala. 6 (1-2), pp. 63 – 89